Risk Analysis of The Implementation of Electricity Infrastructure Construction Case Study: Gistet 500 Kv Payton - Fahmi Kuncoro; Dhimas Widhi Handani (Publikasi Indonesia, 2025)
This research analyzes the construction risks of the 500 kV Paiton High Voltage Substation (GISTET) and develops the most optimal risk treatment based on the risk management standard SNI 8615:2018. The research variables were derived from a literature review, followed by the Delphi Technique questionnaire to identify relevant risks from respondents. Subsequently, a qualitative analysis was conducted using the Consequence/Probability Matrix to identify the dominant risks, followed by a quantitative analysis using the Expected Monetary Value (EMV) calculation. The determination of the most optimal risk treatment for each dominant risk was obtained through Decision Tree Analysis (DTA). The research results identify 38 relevant risks, with 10 classified as dominant, categorized as high, very high, and extreme risks. The three risks with the highest EMV impact values are project execution time not aligning with the project schedule, suboptimal contractor performance, and delays in the arrival and mobilization of materials to be installed. The study's implications underscore the importance of proactive risk management in large-scale construction projects, aiming to minimize potential losses and ensure project success.